Traditional and Nontraditional Mental Healthcare Services: Usage and Preferences Among Adolescents and Younger Adults - Cohen, Katherine A. (J Behav Health Serv Res, 2021)
In recent years, nontraditional mental healthcare services and tools (e.g., mobile apps, peer counselors, online support groups) have been developed to increase access to and utilization of behavioral health services. This study investigates how adolescents and younger adults use and perceive various nontraditional mental healthcare services in comparison to traditional services and in comparison to each other. A questionnaire-based study was conducted that included 203 participants between the ages of 17 and 37 (M = 25.01, SD = 5.04). Results showed that while usage rates of nontraditional mental health services were considerably high, the highest rates were reported for traditional services. Similarly, participants reported high levels of willingness to use nontraditional services, yet the highest levels of willingness were reported for traditional services. These findings suggest that the integration of nontraditional services with traditional services may be particularly impactful for young people. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11414-020-09746-w.